Automação em bibliotecas: desenvolvimento e adaptação de aplicativos - Coelho, Nivaldo Aparecido (Universidade Federal de São Carlos, 2010)
Given the need for development and adaptation of computational solutions as a way to facilitate the academic life of users of Library Service School of Engineering of São Carlos (EESC), University of São Paulo (USP), the objective is to develop and implement solutions in order to fill "gaps" left by library management software. The research method used was action research and as a result was deployed three computing solutions in the organization: 1) Request copies of Production; 2) Renewal and reservation of books; and 3) Loans from libraries. It follows that the solutions are presented as effective tools in increasing the visibility of science produced and services offered by the library of EESC-USP, with use of local human and technological resources.
Automation in libraries: development and application adaptation
Keywords: Automação em bibliotecas; Biblioteca universitária; University libraries; Automation in libraries; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO